POZNAŃ WALDEMARA ŻYSZKIEWICZA - RYDZ, AGNIESZKA (Slavia Occidentalis, 2020)
The article focuses on the theoretical works of Douwe Draaisma, Tomasz Maruszewski and Małgorzata Czermińska. Żyszkiewicz’s poems revolve around the theme of deportees from Lvov settling down after WWII in Poznań, an area where German culture was cultivated. In the poems, a connection is made between the poet’s memory and specific features of the city’s topography.